Screening, isolation and characterization of phenolic compound producing fungi using agricultural waste as substrate - Muhamad Azharuddin, Muhamad Nor (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research focuses on the characterization of fungi producing phenolic compound which is ferulic acid through solid-state fermentation using rice husk and empty fruit bunch as substrates. Screening of isolated fungi by using total phenolic content and feruloyl esterase assays showed that UMAS P2 andUMAS B2 were able to produce phenolic compound which is ferulic acid. The morphological characteristic and molecular identification was done and the result showed that UMAS P2 is Rhizomucor variabilis and UMAS B2 is Fusarium chlamydosporum. Determination of the production of phenolic compound using Rhizomucor variabilis and Fusarium chlamydosporum under solid state fermentation is achieved by total phenolic content, 'while feruloyl esterase assays for the detection of fem lic acid. The production of phenolic compound by Rhizomucor variabilis under solid state fermentation of rice husk and empty fruit bunch was recorded as 0.087 mglg and 0.156 mglg, respectively, while the production of phenolic compound by Fusarium ch/amydosporum under solid state fermentation of rice husk and empty fruit bunch was 0.078 mglg and 0.065 mglg respectively. Besides, the feruloyl esterase activity by Rhizomucor variabilis under solid state fermentation of rice husk and empty fruit bunch was recorded as 1.721 U/g and 0.597 U/g, while the feruloyl esterase activity by Fusarium chlamydosporum under solid state fermentation of rice husk and empty fruit bunch was 1.806 U/g and 1.024 U/g, respectively. In conclusion, Rhizomucor variabilis and Fusarium chlamydosporum have an ability to produce phenolic compound by utilizing agricultural waste such as rice husk and empty fruit bunch as carbon source.